Respuesta :
For this case we have the following expressions:
Monomial: 5x2y
Binomial: (2xy2 + x2y)
Adding we have:
5x2y + (2xy2 + x2y)
= x2y (5 + 1) + 2xy2
= 6x2y + 2xy2
We observe that the result of the sum is a binomial.
Answer:
Binomial: 6x2y + 2xy2
Monomial: 5x2y
Binomial: (2xy2 + x2y)
Adding we have:
5x2y + (2xy2 + x2y)
= x2y (5 + 1) + 2xy2
= 6x2y + 2xy2
We observe that the result of the sum is a binomial.
Answer:
Binomial: 6x2y + 2xy2
Answer:
1. 6x²y+2xy²
2. Binomial
Step-by-step explanation:
Pls mark brainliest! Hope this helps!
☺☻